2021
DOI: 10.3390/agronomy12010037
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Potential of Current Wheat Cultivars and Planting Dates under the Changing Climate in Ethiopia

Abstract: Global warming poses a severe threat to food security in developing countries. In Ethiopia, the primary driver of low wheat productivity is attributed to climate change. Due to the sparsity of observation data, climate-related impact analysis is poorly understood, and the adaptation strategies studied so far have also been insufficient. This study adopted the most popular DSSAT CERES-Wheat model and the ensemble mean of four GCMs to examine the quantitative effects of adjusted sowing dates and varieties on whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
1
0
4
Order By: Relevance
“…This result is in concordance with those of [60], who reported that the early maturing cultivar did not show a yield reduction on any sowing dates, thanks to the earliness of the anthesis stage, on which risk of crop exposure to heat stress during the sensitive grain-filling stage is decreased or avoided. In Ethiopia, [61], reported that by the middle and the end of the 21st century, one wheat cultivar is adapted to late sowing date, under low CO 2 emissions of RCP 4.5, meanwhile another cultivar is well adapted to early sowing date, under elevated CO 2 emissions of RCP 8.5. So, it is important to assess the adaptation of wheat sowing dates under future CC scenarios by simulating different wheat cultivars yields with the crop model in order to select the best-adapted wheat cultivar to the projected CC.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in concordance with those of [60], who reported that the early maturing cultivar did not show a yield reduction on any sowing dates, thanks to the earliness of the anthesis stage, on which risk of crop exposure to heat stress during the sensitive grain-filling stage is decreased or avoided. In Ethiopia, [61], reported that by the middle and the end of the 21st century, one wheat cultivar is adapted to late sowing date, under low CO 2 emissions of RCP 4.5, meanwhile another cultivar is well adapted to early sowing date, under elevated CO 2 emissions of RCP 8.5. So, it is important to assess the adaptation of wheat sowing dates under future CC scenarios by simulating different wheat cultivars yields with the crop model in order to select the best-adapted wheat cultivar to the projected CC.…”
Section: Discussionmentioning
confidence: 99%
“…Экологические испытания -эффективный способ оценки как адаптивности (12,13), так и пластичности сортов (и гомеостатичности урожайности) (14). Выраженность адаптивности сортов обусловлена способностью противостоять действию лимитирующих факторов среды (15)(16)(17)(18)(19) при наличии генетико-физиологических систем адаптивности (ГФСА) (20). Пластичность сорта и поддержание его урожайности по годам зависят от числа ГФСА в геноме (9,(21)(22)(23).…”
unclassified
“…Следует учитывать, что в случае, когда r = 1, ВГС = 0. Это указывает на довольно высокие различия ГФСА, детерминирующих признаки продуктивности (2,(16)(17)(18)(19), которые влияют на формирование урожайности в экологической зоне. Анализ коэффициентов корреляций по годам наблюдений показывает, что в засушливые годы формирование урожайности контролируют другие наборы продуктов генов.…”
unclassified
“…Экологические испытания -эффективный способ оценки как адаптивности (12,13), так и пластичности сортов (и гомеостатичности урожайности) (14). Выраженность адаптивности сортов обусловлена способностью противостоять действию лимитирующих факторов среды (15)(16)(17)(18)(19) при наличии генетико-физиологических систем адаптивности (ГФСА) (20). Пластичность сорта и поддержание его урожайности по годам зависят от числа ГФСА в геноме (9,(21)(22)(23).…”
unclassified
“…Следует учитывать, что в случае, когда r = 1, ВГС = 0. Это указывает на довольно высокие различия ГФСА, детерминирующих признаки продуктивности (2,(16)(17)(18)(19), которые влияют на формирование урожайности в экологической зоне. Анализ коэффициентов корреляций по годам наблюдений показывает, что в засушливые годы формирование урожайности контролируют другие наборы продуктов генов.…”
unclassified